Utility of Estimated Glomerular Filtration Rate in Hypertensive and Type 2 Diabetic Patients: Results from a Community-Based Study - Gutiérrez-León, Eduardo; Santiago, Ricardo Escamilla-; Pacheco-Domínguez, Reyna; Amezcua, Pablo Martínez-; Correa-Rotter, Ricardo; Cervantes, Malaquías López- (Archives of Clinical and Biomedical Research, 2023)
Background: The usefulness of eGFR for screening chronic kidney disease (CKD) in early stages among people with type 2 diabetes (T2D) and hypertension is still under investigation and has not been definitively established. Methods: We used a cross-sectional and longitudinal design and recruited adults over 19 years of age from Hidalgo, Mexico between 2012 and 2016. The study aimed to determine the use of eGFR as a screening method for comorbidity among people with type 2 diabetes and hypertension. The mean difference was compared between periods and longitudinal linear regression models were used to analyze the relationship between eGFR and blood pressure and HbA1c levels, which were divided into quartiles. The results of this study may provide information on the effectiveness of using eGFR for screening chronic kidney disease in this population. Results: They recruited 1721 participants, of whom 102 had T2D, 319 had hypertension, 142 had both, and 208 had neither. The results showed that an increase in blood pressure was associated with a decrease in eGFR across all groups, with the greatest decrease observed in the last quartile compared to the first quartile in the second evaluation, and among those with hypertension only (-14.20, 95% confidence interval [95%CI] -24.33 to -4.08, P 0.001) and those with both T2D and hypertension (-16.06, 95% CI -31.94 to -0.17, P 0.04). The trend in eGFR was more stable in relation to an increase in HbA1c, which was more marked in the second measurement among those with T2D only (2.32, 95%CI -15.11 to 19.74, P≥0.05). The longitudinal analysis of the absolute change in eGFR showed similar trends across all groups. These findings suggest that blood pressure may have a greater impact on eGFR compared to HbA1c levels in this population. Conclusions: The increase in blood pressure is associated with a decrease in eGFR regardless of the presence of T2D or hypertension. This suggests that measuring eGFR over a short period of time (2 years) can be useful in detecting early-stage kidney damage.